Pengaruh Online Customer Rating Dan Online Custumer Review Terhadap Keputusan Pembelian Produk Pakaian Di Aplikasi Shopee Pada Mahasiswa Pendidikan Ekonomi Universitas Hkbp Nommensen Pematang Siantar - Elsa Maria Sihaloho; Debbi Petra Meyana Sitorus; Injen Pardamean Butar-Butar (JOURNAL SAINS STUDENT RESEARCH, 2023)
This study aims to determine the effect of Online Customer Rating and Online Customer Review on Purchasing Decisions for Clothing Products on the Shopee Application for Economic Education Students at HKBP Nommensen University Pematang Siantar. Type of quantitative research. The population in this study were economic education students. The sample of this study amounted to 100 respondents. The sampling technique used is nonprobability sampling technique. The questionnaire test consists of a validity test using the product moment correlation method, a reliability test using Cronbach alpha, a classical assumption test which includes: normality test, multicollinearity test, heteroscedasticity test, and multiple linear regression, t test (partial), and f test (simultaneous). The results showed that: There is a positive but insignificant effect of Online Customer Rating on Purchasing Decisions, this can be seen in the t test where the value of Thitung> Ttabel (1.721> 1.6608) with a significant value of 0.088> 0.05, it can be said that Online Customer Rating has an effect but is not significant on Purchasing Decisions. There is a positive and significant effect of Online Customer Review on Purchasing Decisions, this can be seen in the t test where the value of Thitung > Ttabel (3.935 > 1.6608) with a significant value of 0.000 <0.05, it can be said that Online Customer Review has an effect and is significant on Purchasing Decisions. Online Customer Rating and Online Customer Review together influence Purchasing Decisions, this can be seen in the F test fcount > ftabel (20.399 > 3.09203). The coefficient of determination test is known to be 0.296, which means that 29.6% of the Online Customer Rating and Online Customer Review variables affect the decision to purchase clothing products in the shoppe application for economic education students at HKBP Nommensen Pematangsiantar University.